Elevated Proportions of Circulating CXCR5+ Follicular Helper T Cells Reflect the Presence of Airway Obstruction in Asthma - Tsukie Kin Tsukuda; Kimiko Tsuji; Akari Nishimori; Takehiko Ito; Yuka Kobayashi; Taro Suzuki; Akihito Yokoyama (Journal of Immunology Research)
Rationale. The progressive decline in lung function observed in asthma is attributed to persistent type 2 airway inflammation and associated airway remodeling. While various immune cells are involved in localized type 2 airway inflammation, whether these reflect the presence of airway obstruction due to persistent type 2 airway inflammation remains unclear. This study aimed to explore whether the proportions of immune cells in peripheral blood indicate the presence of type 2 inflammation and airway obstruction in asthmatics. Materials and Methods. Using flow cytometry, we identified and quantified Group 2 innate lymphocytes, T helper 2 cells, follicular helper T cells, and T helper 17 cells in peripheral blood samples from 49 individuals with asthma. We then conducted cross-sectional analyses to assess relationships between levels of these immune cells and lung function parameters, including the percentage predicted forced expiratory volume in 1 s (%FEV1). We also examined correlations between the proportions of immune cells and type 2 biomarkers. Results. Proportions of CXCR5+ follicular helper T cells in human peripheral blood, as opposed to Group 2 innate lymphoid cells (ILC2) or T helper 2 cells, were significantly higher in cases with %FEV1 < 80% compared to those with %FEV1 ≥ 80%. Further, these proportions correlated negatively with %FEV1 and positively with blood eosinophil counts. Conclusions. The proportion of circulating follicular helper T cells, but not T helper 2 cells or Group 2 innate lymphoid cells, may reflect the presence of airway obstruction caused by persistent type 2 inflammation.